2007
DOI: 10.1108/13527600710745750
|View full text |Cite
|
Sign up to set email alerts
|

Cultural distance asymmetry in expatriate adjustment

Abstract: Purpose -The current literature implicitly assumes a symmetric impact of cultural distance (CD) on expatriate adjustment. By using distance as a predictor of adjustment, the literature has rendered the direction of the flow irrelevant: a US expatriate in Germany is presumed to face the same hurdle as a German expatriate in the USA. Not only is there no evidence to justify that suggestion, but logic and related findings suggest just the opposite. The aim of the present paper is to test the proposition that such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 41 publications
7
88
1
2
Order By: Relevance
“…Shenkar (2001) pointed out that the cultural distance perceived by a Dutch firm investing in China is not the same distance faced by a Chinese firm investing in the Netherlands. In a study on expatriates, Selmer et al (2007) concluded that German expatriates assigned to the US were better adjusted than US expatriates assigned to Germany. Håkanson and Ambos (2010) argued that managers from a country with a well-defined regulatory environment and transparent governance structures experience huge difficulties in countries with weak formal institutions.…”
Section: Symmetric and Asymmetric Proximities In Mandamentioning
confidence: 99%
“…Shenkar (2001) pointed out that the cultural distance perceived by a Dutch firm investing in China is not the same distance faced by a Chinese firm investing in the Netherlands. In a study on expatriates, Selmer et al (2007) concluded that German expatriates assigned to the US were better adjusted than US expatriates assigned to Germany. Håkanson and Ambos (2010) argued that managers from a country with a well-defined regulatory environment and transparent governance structures experience huge difficulties in countries with weak formal institutions.…”
Section: Symmetric and Asymmetric Proximities In Mandamentioning
confidence: 99%
“…Our theoretical arguments are in line with previous scholars who noted problems with symmetry in general (e.g., Tversky, 1977) and specifically with respect to cultural distance (e.g., Chapman et al, 2008;Shenkar, 2001;Tung & Verbeke, 2010). The empirical results are also consistent with observed asymmetries in various functional areas of MNC-management such as expatriate deployment (Brock et al, 2008) and adjustment (Selmer et al, 2007), control modes of cooperation (Lee, Shenkar, & Li, 2008), and joint venture control and performance (Luo et al, 2001). Our results also argue for the need to truly consider both country distance and country relatedness as asymmetric in international business research.…”
Section: Discussionsupporting
confidence: 80%
“…Also, conceptualizations of country distance that do not involve the decisions made by real managers are not able to reproduce the dynamic interaction of MNEs with their host country environments (e.g., Shenkar, Luo, & Yeheskel, 2008) and disregard the fact that strategies are formulated by managers based on their perceptions of markets and the fit with their firm specific resources (Tallman, 1992). Finally, as many authors have argued, and empirical evidence has demonstrated, several of the assumptions made in the research on country distance are violated in the real world (e.g., Brock, Shenkar, Shoham, & Siscovick, 2008;Chapman, Gajewska-De Mattos, Clegg, & Buckley, 2008;Luo, Shenkar, & Nyaw, 2001;Selmer, Chiu, & Shenkar, 2007;Shenkar, 2001). …”
Section: Country Relatednessmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuing empirical papers by Selmer et al (2007), Brock et al (2008) and Lee et al (2008) deal with specific operationalization problems of the cultural distance concept, such as the 'illusion of symmetry'. Two additional conceptual papers by Shenkar et al (2008) provide a more pronounced critique of the cultural distance concept itself (in particular Shenkar et al 2008) and the further development of the closely related cultural friction concept (in particular Luo and Shenkar 2011).…”
Section: Introductionmentioning
confidence: 99%